Expressive Acts in Euphoria Special Episode Part 1: Trouble Don’t Last Always - Nasution, Hotman; Ambalegin, Ambalegin (e-Journal of Linguistics; Vol 16 No 2 (2022): ejl-July, 2022)
The research identifies the type of expressive acts uttered by the characters in a special episode entitled Euphoria Part 1: Rue – Trouble Don’t Last Always and the research implements Norrick theory to analyze the data. Then, the research designs the activity in qualitative method which shapes how the report of the analysis would be descriptively. In collecting the data, the research appropriates Observational method and non-participation technique by Sudaryanto. On the other hand, in analyzing the data, the research appropriates Pragmatic Identity Method and Matching technique by Sudaryanto. The research found 26 utterances identified completely of the types of expressive acts; (2) apologizing, (1) thanking, (1) congratulating, (4) condoling, (5) deploring, (8) lamenting, (2) welcoming, (2) forgiving, and (1) boasting. Lamenting is the most frequent expressive act as the central story of the episode where the main character shared their sorrow and regret to their friend.